Acromioclavicular Joint Injuries in the National Football League: Epidemiology and Management. (December 2013) - Lynch, T. Sean; Saltzman, Matthew D.; Ghodasra, Jason H.; Bilimoria, Karl Y.; Bowen, Mark K.; Nuber, Gordon W.
Background: Previous studies investigating acromioclavicular (AC) joint injuries in professional American football players have only been reported on quarterbacks during the 1980s and 1990s. These injuries have not been evaluated across all position players in the National Football League (NFL). Purpose: The purpose of this study was 4-fold: (1) to determine the incidence of AC joint injuries among all NFL position players; (2) to investigate whether player position, competition setting, type of play, and playing surface put an athlete at an increased risk for this type of injury; (3) to determine the incidence of operative and nonoperative management of these injuries; and (4) to compare the time missed for injuries treated nonoperatively to the time missed for injuries requiring surgical intervention. Study Design: Descriptive epidemiological study. Methods: All documented injuries of the AC joint were retrospectively analyzed using the NFL Injury Surveillance System (NFLISS) over a 12-season period from 2000 through 2011. The data were analyzed by the anatomic location, player position, field conditions, type of play, requirement of surgical management, days missed per injury, and injury incidence. Results: Over 12 NFL seasons, there were a total of 2486 shoulder injuries, with 727 (29.2%) of these injuries involving the AC joint. The overall rate of AC joint injuries in these athletes was 26.1 injuries per 10, 000 athlete exposures, with the majority of these injuries occurring during game activity on natural grass surfaces (incidence density ratio, 0.79) and most often during passing plays. These injuries occurred most frequently in defensive backs, wide receivers, and special teams players; however, the incidence of these injuries was greatest in quarterbacks (20.9 injuries per 100 players), followed by special teams players (20.7/100) and wide receivers (16.5/100). Overall, these athletes lost a mean of 9.8 days per injury, with quarterbacks losing the most time to injury (mean, 17.3 days). The majority of these injuries were low-grade AC joint sprains that were treated with nonoperative measures; only 13 (1.7%) required surgical management. Players who underwent surgical management lost a mean of 56.2 days. Conclusion: Shoulder injuries, particularly those of the AC joint, occur frequently in the NFL. These injuries can result in time lost but rarely require operative management. Quarterbacks had the highest incidence of injury; however, this incidence is lower than in previous investigations that evaluated these injuries during the 1980s and 1990s.